Reduced levels of NGF shift astrocytes toward a neurotoxic phenotype - Tiberi, Alexia; Carucci, Nicola Maria; Testa, Giovanna; Rizzi, Caterina; Pacifico, Paola; Borgonovo, Giulia; Arisi, Ivan; D’Onofrio, Mara; Brandi, Rossella; Gan, Wen-Biao; Capsoni, Simona; Cattaneo, Antonino (Frontiers in Cell and Developmental Biology, 2023)
Nerve growth factor (NGF) is critical for neuronal physiology during development and adulthood. Despite the well-recognized effect of NGF on neurons, less is known about whether NGF can actually affect other cell types in the central nervous system (CNS). In this work, we show that astrocytes are susceptible to changes in ambient levels of NGF. First, we observe that interfering with NGF signaling in vivo via the constitutive expression of an antiNGF antibody induces astrocytic atrophy. A similar asthenic phenotype is encountered in an uncleavable proNGF transgenic mouse model (TgproNGF#72), effectively increasing the brain proNGF levels. To examine whether this effect on astrocytes is cell-autonomous, we cultured wild-type primary astrocytes in the presence of antiNGF antibodies, uncovering that a short incubation period is sufficient to potently and rapidly trigger calcium oscillations. Acute induction of calcium oscillations by antiNGF antibodies is followed by progressive morphological changes similar to those observed in antiNGF AD11 mice. Conversely, incubation with mature NGF has no effect on either calcium activity nor on astrocytic morphology. At longer timescales, transcriptomic analysis revealed that NGF-deprived astrocytes acquire a proinflammatory profile. In particular, antiNGF-treated astrocytes show upregulation of neurotoxic transcripts and downregulation of neuroprotective mRNAs. Consistent with that data, culturing wild-type neurons in the presence of NGF-deprived astrocytes leads to neuronal cell death. Finally, we report that in both awake and anesthetized mice, astrocytes in layer I of the motor cortex respond with an increase in calcium activity to acute NGF inhibition using either NGF-neutralizing antibodies or a TrkA-Fc NGF scavenger. Moreover, in vivo calcium imaging in the cortex of the 5xFAD neurodegeneration mouse model shows an increased level of spontaneous calcium activity in astrocytes, which is significantly reduced after acute administration of NGF. In conclusion, we unveil a novel neurotoxic mechanism driven by astrocytes, triggered by their sensing and reacting to changes in the levels of ambient NGF.